Potential Drug Target Identification in Porphyromonas gingivalis using In-silico Subtractive Metabolic Pathway Analysis - Sao, Prachi; Chand, Yamini; Kumar, Atul; Singh, Sachidanand (Bangladesh Journal of Medical Science, 2021)
Introduction: Porphyromonas Gingivalis (P. gingivalis) a primary periodontal disease pathogen. This bacterium affects sub-gingival tissue and leads to loss of teeth and alveolar bone destruction in the acute stage. In recent years, P. gingivalis is often connected with other diseases such as rheumatoid arthritis, diabetes, Alzheimer’s, and heart disease, though the aetiology is still unclear. Objective: The use of commonly available drugs to treat periodontitis results in various side effects, in particular multi-drug resistant strains. As the development of multidrugresistant strains frequently urges the identification of novel drug targets, the aim of this study is to identify specific targets in the narrow spectrum to combat oral pathogens. Methodology: This study used a comparative and subtractive pathway analysis approach to identify potential drug targets specific to P. gingivalis. Results: The in-silico comparison of the P. gingivalis and Homo sapiens (H. sapiens) metabolic pathways resulted in 13 unique pathogen pathways. A homology search of the 67 enzymes in the unique bacterial pathway using the BLASTp program against the Homo sapiens proteome resulted in fifteen possible targets that are non-homologous to the human proteome. Thirteen genes among 15 potent target encoders are key DEG genes indispensable for P. gingivalis’s survival. A comprehensive analysis of the literature identified three potential therapeutic drug targets. Conclusions: The three most relevant drug targets are Arabinose-5-phosphate isomerase, UDP-2,3-diacylglucosamine hydrolase, and Undecaprenyl diphosphatase. Upon corroboration, these targets may give rise to narrow-spectrum antibiotics that can specificallytreat thedental infection. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.887-896